2015
DOI: 10.3791/53129
|View full text |Cite
|
Sign up to set email alerts
|

MRI-guided dmPFC-rTMS as a Treatment for Treatment-resistant Major Depressive Disorder

Abstract: Here we outline the protocol for magnetic resonance imaging (MRI) guided repetitive transcranial magnetic stimulation (rTMS) to the dorsal medial prefrontal cortex (dmPFC) in patients with major depressive disorder (MDD). Technicians used a neuronavigation system to process patient MRIs to generate a 3-dimensional head model. The head model was subsequently used to identify patient-specific stimulatory targets. The dmPFC was stimulated daily for 20 sessions. Stimulation intensity was titrated to address scalp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Although they are not significant when analyzing response rates (48.5% vs. 50.6%, respectively), they become more evident when examining remission rates (27.9% vs. 38.5%, respectively) . In spite of this, the combination of the two techniques in the same session (6000 pulses at 10 Hz + 1200 pulses of iTBS) does not appear to supply any additional gains in either response (44%) or remission (34.7%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are not significant when analyzing response rates (48.5% vs. 50.6%, respectively), they become more evident when examining remission rates (27.9% vs. 38.5%, respectively) . In spite of this, the combination of the two techniques in the same session (6000 pulses at 10 Hz + 1200 pulses of iTBS) does not appear to supply any additional gains in either response (44%) or remission (34.7%) .…”
Section: Discussionmentioning
confidence: 99%
“…The daily combination of 10 Hz DC-TMS with iTBS by a DC coil, both over the dmPFC, achieved 44% response and 34.78% remission after 20 or 30 sessions in a group of 25 individuals with unipolar or bipolar TRD included in an open label clinical trial. The authors described mild scalp discomfort and pain at the site of stimulation that was adequately managed using adaptive titration (20). However, the comparison between the two techniques (10 Hz vs. iTBS), performed in a retrospective series of 185 cases, found no relevant differences between the treatment groups despite the existence of a slight advantage for the 10 Hz stimulation in response (10 Hz: 50.6% vs. iTBS: 48.5%) and remission (10 Hz: 38.5% vs. iTBS: 27.9%).…”
Section: Wwwneuromodulationjournalcommentioning
confidence: 99%
“…All patients underwent rTMS targeting the DMPFC according to previously described methods (Dunlop et al, 2015a;Salomons et al, 2014), with a course length of 20 sessions extended to 30 sessions in treatment responders (mean number of sessions 24.29, 6 SD 5.14). Participants completed two standardized self-report questionnaires at pretreatment and posttreatment: the PTSD Checklist-Civilian version (PCL-C) (Weathers, Litz, Huska, & Keane, 1994) and the Difficulties with Emotional Regulation Scale (DERS) (Gratz & Roemer, 2004).…”
Section: E Th Odsmentioning
confidence: 99%
“…Based on this finding 10 Hz dmPFC‐DCC‐rTMS has mainly been applied for the treatment of depression . Practically all available studies suggest an antidepressant effect , although only one study has been sham‐controlled . Moreover, imaging studies revealed brain connectivity changes in treatment responders without a clear pattern across studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Hz rTMS with the DCC over the mPFC has been shown to increase cerebral blood flow in the dACC (12). Based on this finding 10 Hz dmPFC-DCC-rTMS has mainly been applied for the treatment of depression (57,62,63,68). Practically all available studies suggest an antidepressant effect (57,62,63,68), although only one study has been sham-controlled (68).…”
Section: The Impact Of Stimulation Protocolsmentioning
confidence: 99%